Removal of adult subconjunctival Loa loa amongst urban dwellers in Nigeria. - Ogugua Ndubuisi Okonkwo; Adekunle Olubola Hassan; Taofik Alarape; Toyin Akanbi; Olufemi Oderinlo; Ayodele Akinye; Idris Oyekunle (Public Library of Science (PLoS), 2018)
Loiasis is a neglected tropical disease caused by infection with the filarial parasite Loa loa. It is a disease considered by many to be benign. Several reports of trans border importation of the Loa loa worm amongst immigrants and visitors from endemic regions of the world exist. In most cases an adult subconjunctival worm is removed from the patient. An interventional case series is reported and examines the practice of removal of subconjunctival adult Loa loa worms amongst urban dwellers in Nigeria. Four cases of ocular loiasis seen amongst urban dwellers in Nigeria exemplify the different presentations and removal methods of the subconjunctival adult worm. There were 2 males and 2 females aged 35years, 23years, 25years and 30years respectively. Each patient gave a history of having been raised in a rural community in childhood years, during which they were exposed to streams and muddy farm land; and then migrated to the urban community in later years. They all present with the finding of a subconjunctival adult worm, which was successfully removed and identified to be Loa loa. There are more urban dwellers in Nigeria who present with symptoms of foreign body sensation that may be related to the manifestation of a subconjunctival worm and are not recognized. This is because the emphasis on this disease has erstwhile been on the rural, village dwellers and not on urban dwellers. Eye care practitioners working in urban centers need to be aware of the possibility of this presentation, and be ready to remove any subconjunctival worm when it presents.